Assessing the dependency of Finland and the EU on Chinese imports - Juuso Kaaresvirta; Eeva Kerola; Riikka Nuutilainen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This policy brief provides an overview of Finland's dependency on imports from China in both a national and EU context. As trade figures based on value added only provide a rough notion of China's contribution to final consumption, we also consider import dependence from the goods imports figures of Finnish Customs to assess import dependence directly for specific product groups. As many products of Chinese origin are imported as semifinished goods or components for products finished in another EU country, we break down also the import dependency of the EU on China by specific product groups. We then compare Finland's domestic production of select industrial product groups against comparable imports from China. We analyze Finland's dependence on China for critical raw materials and identify potential alternative sources for key product groups for which Finland and the EU are currently dependent on China.
urn:nbn:fi-fe2023033134219
Keywords: 330; China; Finland; EU; foreign trade; imports; dependency